A Case of Suspicious Allergic Reaction to Peracetic Acid Following Endoscopy - Naohiko Harada; Manami Hirowatari; Eikichi Ihara; Etsuko Ishihara; Mitsuko Inoue; Tomoya Miyamura; Makoto Nakamuta (Korean Society of Gastrointestinal Endoscopy, 2020)
A 43-year-old man with rheumatic arthritis was admitted to our hospital for symptoms of cough, left chest pain, and left elbow pain, and further examination revealed an elevated level of C-reactive protein. On day 2 after admission, he underwent esophagogastroduodenoscopy. On the morning of day 7, he developed a high fever of 39.7°C, several hours after bronchoscopy. On day 13, he underwent colonoscopy. Five minutes after the colonoscopy, he developed a high fever of 39.9°C, accompanied by stridor, indicating a decrease in arterial oxygen saturation level. An intradermal test for peracetic acid which was used for cleaning flexible endoscopy was positive. We suspect that he suffered from an allergic reaction to peracetic acid following the flexible endoscopy. This is the first case reported on suspicious allergic reaction to peracetic acid following a flexible endoscopy procedure.